The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/13607863.2015.1065791
|View full text |Cite
|
Sign up to set email alerts
|

Issues in research on aging and suicide

Abstract: Late-life suicide is a complex clinical and public health problem. In this article, some of the key complexities inherent in studying late-life suicide are discussed in the service of promoting high quality late-life suicide prevention science. We discuss the following research issues: the relatively greater lethality of suicidal behavior in later life (compared to younger ages); the lack of data on whether thoughts of death in later life are indicators of suicide risk; the fact that older adults do not tend t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
58
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 106 publications
1
58
0
2
Order By: Relevance
“…Our search returned 25 papers relevant to one or more review question spanning 11 countries with the majority focusing exclusively on depression and notably less emphasis on self-harm or suicidal behavior. None of the studies reviewed offered a theoretical explanation of mental health decline in this population despite more than half reporting on interventions to improve or support mental health, a criticism noted by other authors in this area (Van Orden & Conwell, 2016). However, some of the studies indicated that transitioning from independent living to a residential setting is likely to be a significant risk factor for poor mental health in this population (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Our search returned 25 papers relevant to one or more review question spanning 11 countries with the majority focusing exclusively on depression and notably less emphasis on self-harm or suicidal behavior. None of the studies reviewed offered a theoretical explanation of mental health decline in this population despite more than half reporting on interventions to improve or support mental health, a criticism noted by other authors in this area (Van Orden & Conwell, 2016). However, some of the studies indicated that transitioning from independent living to a residential setting is likely to be a significant risk factor for poor mental health in this population (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, the findings are striking enough that it is likely that there are true age‐related differences in screening practices between individuals able to answer. The low rate of positive self‐harm, SI, or SA in older adults is interesting, given high suicide rates in older adults and prior work demonstrating high risk of SI and SA after ED or hospital contact and in individuals with physical impairments or declining health (both common in older adults in the ED) . Thus, the current study findings suggest the need for improved provider awareness about risk of suicide in older adults (and the need to screen for it) and enhanced identification systems (e.g., possible adjustment of the screening questions used for older adults).…”
Section: Discussionmentioning
confidence: 74%
“…Whereas targeted interventions in primary care settings have been shown to improve screening and effective treatment for depression, less is known about these approaches in the ED. Older adults in the ED with mental health reasons for an ED visit are more likely to be admitted than younger individuals, but we do not know whether the general prevalence or patterns of SI and SA differ from those in younger or middle‐aged adult populations.…”
mentioning
confidence: 99%
“…In the US, approximately half a million patients present annually to EDs for treatment of deliberate self-harm, 1 which includes intentional self-injury and self-poisoning irrespective of suicidal intent. 9 Prior research suggests that a large majority of self-harm events in older adults are suicide attempts, [10][11][12] rather than nonsuicidal selfinjury which is more prevalent in younger persons. 2,3 Suicide risk increases substantially after age 65,4 and the geriatric population is growing rapidly.…”
mentioning
confidence: 99%
“…8 As compared with younger adults, suicide prevention in older adults tends to be more challenging because self-harm behavior is more immediately lethal and has fewer warning signs. 9 Prior research suggests that a large majority of self-harm events in older adults are suicide attempts, [10][11][12] rather than nonsuicidal selfinjury which is more prevalent in younger persons. [13][14][15] In the US, the prevalence of ED visits for self-harm peaks in early adulthood then decreases with age.…”
mentioning
confidence: 99%